Human finitude and Nursing: hermeneutic reflections in the light of Gadamer's thought (Research, Society and Development, 2020)
This manuscript presents reflections on aspects of the finitude of life under Gadamer's hermeneutics and the relationship with the nursing before the experience of death of patients under its care. This is a descriptive study type reflective analysis of the literature. Death is a theme present in discussions in various areas of knowledge and directly affects the way of living and dying of humans. Only the human being possesses the awareness about the death itself and this understanding ends up generating anxiety, fear and pain. The finitude of life is seen under different aspects, both by patients and by the nurse who meets the patient, and this professional tends to limit the discussion to purely technical aspects. In nursing care, there is need to consider these issues, bringing a more humanized assistance, with a quality listening and minimizing the impact that death brings to the family. There is also need to think about the knowledge gap during the academic training of these professionals and encourage discussions on the topic. Thus, the expectation is to contribute to the reflection of the practices and care of nurses in the death process.